Tantangan dan Peluang Pembangunan Proyek Pembangkit Listrik Energi Baru Terbarukan (EBT) di Indonesia - Mohammad Ahsan (Sutet, 2021)
The purpose of this study is to find out the current state of Indonesia's electricity with New and Renewable Energy, analyze the challenges in the development of New and Renewable Energy, and analyze opportunities to develop Indonesia's electricity through sustainable development of New and Renewable Energy. Energy generation, analyzing the factors that support the development of New and Renewable Energy plants and analyzing the effect of economic growth, customer growth, connected power, and electricity sales with the development of New and Renewable Energy. The research design and methodology used are qualitative and quantitative methods by looking at the relationship between the variables of economic growth, plant growth, customer additions, and electricity sales related to the development of New and Renewable Energy in Indonesia. The findings in this study are that the construction of New and Renewable Energy plants is needed to answer environmental challenges and the company's growth, especially the increase in the number of customers, connected power and electricity sales. These findings provide an initial overview of systemic variables and patterns in the development of New and Renewable Energy in Indonesia.